2018
DOI: 10.1080/14681994.2018.1549361
|View full text |Cite
|
Sign up to set email alerts
|

Facing polyamorous lives: translation and validation of the attitudes towards polyamory scale in a Portuguese sample

Abstract: Consensual Non-Monogamies (CNMs) have been receiving the attention of academics, however attitudes towards polyamory are still a new field of research. We aim at studying the reliability and validity of the Attitudes Towards Polyamory (ATP) scale in a Portuguese sample. The present analysis utilized cross-sectional data from 609 volunteers that completed the online survey. After randomly splitting the sample (1:1) for cross-validation purposes, Exploratory (EFA) and Confirmatory factor analysis (CFA) were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…The study received ethical and deontological approval by the Comissão de Ética e Deontologia da Investigação Científica da Escola de Psicologia e de Ciências da Vida da Universidade Lusófona de Humanidades e Tecnologias. The data analyzed on this study was gathered within the scope of a larger study, that has resulted in previous publication (Cardoso, Pascoal, & Rosa, 2018). This larger study gathered both qualitative and quantitative data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study received ethical and deontological approval by the Comissão de Ética e Deontologia da Investigação Científica da Escola de Psicologia e de Ciências da Vida da Universidade Lusófona de Humanidades e Tecnologias. The data analyzed on this study was gathered within the scope of a larger study, that has resulted in previous publication (Cardoso, Pascoal, & Rosa, 2018). This larger study gathered both qualitative and quantitative data.…”
Section: Methodsmentioning
confidence: 99%
“…These assertions are made despite evidence against them, as health and happiness levels reported by people in non-monogamous relationships are equal to or higher than those of people in monogamous relationships (Conley et al, 2012 , 2013 ; Fleckenstein & Cox, 2015 ). However, stigma prevents proper health care from being delivered to polyamorous persons that could arguably suffer from minority stress (Meyer, 2003 ), as research seems to indicate (Cardoso et al, 2020 ), and this minority stress may be amplified by the expectation of encountering prejudice and rejection by social groups, or health care professionals (McCrosky, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to understanding lifetime prevalence of polyamory in the present study, we probed whether people desire to engage in polyamory. Recent research using convenience samples has examined willingness or desire to engage in consensual non-monogamy (e.g., Moors et al, 2015 ; Cardoso et al, 2020 ). Moors et al (2015) found that among heterosexually identified people who had never engaged in consensual non-monogamy, men expressed greater willingness than women to engage in all three popular consensual non-monogamy sub-types.…”
Section: Interest and Engagement In Consensual Non-monogamymentioning
confidence: 99%
“…Although interest in sexual practices is not a direct assessment of willingness, these estimates help provide a proxy to interest in some types of consensual non-monogamy (e.g., swinging). Indeed, recent research has documented that positive attitudes toward consensually non-monogamous relationships predict greater willingness to engage in these relationships ( Cardoso et al, 2020 ).…”
Section: Interest and Engagement In Consensual Non-monogamymentioning
confidence: 99%
“…Geralmente, pesquisadores apresentam resultados juntamente com cálculo de alfa, caso um dos itens seja removido, avaliando se o valor total do coeficiente aumenta ou diminui (16) com a remoção daquele item. Deste modo, se o alpha de Cronbach total aumenta significativamente (>0,1), quando o item é removido, há indício de que este não seja consistente com os demais, prejudicando a consistência interna da escala (17) . Destaca-se que a baixa correlação item-total (<0,3) (17) , observada nos itens 2,6,10,12,14,17,18,20,28 e 30, não resultou em elevação do alpha de Cronbach geral, se fossem removidos.…”
Section: Discussionunclassified